Strategi Penyiapan Lulusan SMA Siap Kerja Melalui Program Double Track Di SMAN 1 Lenteng Sumenep - Ainul Hayat; Zumrotun Nisaa Ul-Jannah (Journal Of Human And Education (JAHE), 2026)
A strategy to prepare high school graduates who do not pursue higher education to remain competitive in the workforce, thereby reducing educated unemployment through edupreneurship. This descriptive study employs a qualitative approach involving observation, interviews, and documentation. The observations in this study were supplemented by interviews with three informants actively involved in enhancing the edupreneurship strategies implemented by SMAN 1 Lenteng, supported by existing documentation. The results of this study indicate that SMAN 1 Lenteng, in its efforts to prepare its graduates, has implemented a double-track program to prepare them for the workforce and has collaborated with the business and industrial sectors to ensure the program’s success. The program’s strategy is to foster students’ entrepreneurial spirit by conducting outreach through a “double-track mobile” initiative outside the school and, of course, by leveraging local wisdom found in the surrounding community. Through this program, students who enter the workforce directly can acquire the skills needed to work or start their own businesses. Keywords: Strategy, Double Track, Edupreneurship.